2016
DOI: 10.1039/c6ew00030d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigators series: microbial communities in full-scale drinking water distribution systems – a meta-analysis

Abstract: In this study, we co-analyze all available 16S rRNA gene sequencing studies from bulk drinking water samples in full-scale drinking water distribution systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
86
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 83 publications
(123 reference statements)
18
86
3
Order By: Relevance
“…In line with other studies (Pinto et al, 2012;Prest et al, 2014;Wu et al, 2015) phyla such as Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, Bacteroidetes, and Nitrospirae were commonly found in the water samples investigated. As also observed in this study, several studies have identified Proteobacteria as the most abundant phylum in aquatic environments within the drinking water production industry (Bautista-de los Santos et al, 2016;El-Chakhtoura et al, 2015;Liu et al, 2014;Vaz-Moreira, Nunes, & Manaia, 2017;Zanacic, McMartin, & Stavrinides, 2017). It is clear from our results that the bacterial community composition of surface water strongly differs from those of the other water types studied.…”
Section: (A) (B)supporting
confidence: 82%
“…In line with other studies (Pinto et al, 2012;Prest et al, 2014;Wu et al, 2015) phyla such as Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, Bacteroidetes, and Nitrospirae were commonly found in the water samples investigated. As also observed in this study, several studies have identified Proteobacteria as the most abundant phylum in aquatic environments within the drinking water production industry (Bautista-de los Santos et al, 2016;El-Chakhtoura et al, 2015;Liu et al, 2014;Vaz-Moreira, Nunes, & Manaia, 2017;Zanacic, McMartin, & Stavrinides, 2017). It is clear from our results that the bacterial community composition of surface water strongly differs from those of the other water types studied.…”
Section: (A) (B)supporting
confidence: 82%
“…Low abundance of mycobacteria (c. 0Á01À1%) in Finnish biofilms has been reported before (Torvinen et al 2004). This contrast with the high abundance in biofilms of chlorinated systems reported elsewhere (9-38%) Bautista-de los Santos et al 2016), including a pilot study with high (5 mg l À1 ) chlorine dosing where most of the bacterial community composed of mycobacteria (Norton et al 2004). Despite low abundances and lower detection limits on rare members in NGS analysis, the results from this study indicated 10 times less of Mycobacterium spp.…”
Section: Pipe Materials Can Affect Important Rare Microbial Members Incontrasting
confidence: 57%
“…In a study of 14 full‐scale systems, the number of OTUs was higher in disinfectant residual‐free than chlorinated or chloraminated water (Bautista‐de los Santos et al . ). In our study, we focused on biofilms, in which the bacteria can be more resistant to disinfectants than in bulk water, and the species richness and diversity in extra‐disinfected biofilms were significantly lower (26 to 35%) than in regularly disinfected control biofilms by all indexes (Chao1 400 vs 620, Shannon 2·7 vs 4·0, Simpson 0·6 vs 0·8) in active populations (rRNA library).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations